Mixing Techniques: Between Technical Precision and Artistic Intent - TINT, Marc Alexandru; DRĂGULIN, Stela (Studia Universitatis Babes-Bolyai Musica, 2025)
Mixing is a critical phase in music production, defining a track’s sonic character and commercial appeal. Engineers employ EQ, compression, saturation, reverb, and automation to shape the final sound, adapting techniques to each genre’s distinct requirements. Pop music prioritizes vocal clarity, autotune, and harmonic layering, while rock relies on dynamic contrast, distortion, and analogue warmth. Jazz and folk emphasize natural acoustics with minimal processing, whereas electronic and dance music demand precise bass control and rhythmic cohesion. Industry leaders like Dave Pensado, known for innovative digital processing, and Stuart White, recognized for his efficiency and depth, exemplify the diverse approaches to mixing. Michael Brauer’s multi-bus compression technique highlights the blend of technical precision and artistic intuition. As genres evolve, mixing continues to adapt, ensuring music remains both commercially competitive and emotionally compelling.